ENGLISH INTONATION IN READING ALOUD PRODUCED BY THE STUDENTS OF ENGLISH EDUCATION DEPARTMENT AT UNISMUH MAKASSAR - Rezkia; Sujariati; Saiful (Journal of Language Testing and Assessment, 2021)
This research is aimed to determine the kinds of English Intonation used by students when reading aloud. This research was descriptive qualitative. The population were 20 students at the third semester students of English Education Department in UNISMUH Makassar. The instrument used reading text and recording.The result showed that the English intonation used by students when reading aloud a text was very different and varied and the intonation they used was not only rising and falling intonation but also rising falling intonation in some word. Good and correct intonation is very influential on the comfort and for hearing easy to get the meaning of a text.